Adiponectin promotes syncytialisation of BeWo cell line and primary trophoblast cells - Dieudonné Marie-Noëlle; Pecquery René; De Mazancourt Philippe; Leneveu Marie-Christine; Santos Esther; Benaitreau Delphine (BMC, 2010)
Abstract Background In human pregnancy, a correct placentation depends on trophoblast proliferation, differentiation, migration and invasion. These processes are highly regulated by placental hormones, growth factors and cytokines. Recently, we have shown that adiponectin, an adipokine, has anti-proliferative effects on trophoblastic cells. Here, we complete this study by demonstrating that adiponectin modulates BeWo and human villous cytotrophoblast cell differentiation. Results We showed that hCG secretion was up-regulated by adiponectin treatment in both BeWo cells and human cytotrophoblasts from very early placentas (5-6 weeks). The expression of two trophoblast differentiation markers, leptin and syncytin 2, was also up-regulated by adiponectin in BeWo cells. Moreover, adiponectin treatment induced a loss of E-cadherin staining in these cells. In parallel, we demonstrated that AdipoR1 and AdipoR2 are up-regulated during forskolin induced BeWo cell differentiation, reinforcing the role of adiponectin in trophoblast syncytialization. SiRNA mediated down-regulation of AdipoR1 and AdipoR2 was used to demonstrate that adiponectin effects on differentiation were essentially mediated by these receptors. Finally, using a specific inhibitor, we demonstrated that the PKA signalling pathway could be one pathway involved in adiponectin effects on trophoblast differentiation. Conclusion Adiponectin enhances the differentiation process of trophoblast cells and could thus be involved in functional syncytiotrophoblast formation.